2022
DOI: 10.1097/bto.0000000000000579
|View full text |Cite
|
Sign up to set email alerts
|

Transosseous Suture With an All-FiberWire Technique in Patellar Fracture Fixation

Abstract: Background: Patellar fractures account for 0.5% to 1.5% of all bone fractures. Tension band wiring with heavy gauge steel wire and K-wires is traditionally procedure for treating patellar fractures. However, this method is associated with implant-related complications. Present study aimed to evaluate functional clinical outcomes of patellar fracture fixation with transosseous suture using an all-FiberWire technique.Methods: This was a retrospective study involving 16 patellar fractures patients were repaired b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…21 Several other clinical comparisons of suture repair vs wire fixation have reported satisfactory clinical outcomes but with fewer postoperative complications in suture methods. [23][24][25][26][27][28] The results of the present study show consistency with those of a previous study comparing the different wiring methods in a feline patella fracture cadaveric model, in that the CFEW group was stronger than the PTBW group. 10 In this previous study, the CFEW group showed a 1.31-fold greater mean maximum failure load than that of the PTBW group, while in the present study, it was approximately 1.19-fold greater.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…21 Several other clinical comparisons of suture repair vs wire fixation have reported satisfactory clinical outcomes but with fewer postoperative complications in suture methods. [23][24][25][26][27][28] The results of the present study show consistency with those of a previous study comparing the different wiring methods in a feline patella fracture cadaveric model, in that the CFEW group was stronger than the PTBW group. 10 In this previous study, the CFEW group showed a 1.31-fold greater mean maximum failure load than that of the PTBW group, while in the present study, it was approximately 1.19-fold greater.…”
Section: Discussionsupporting
confidence: 89%
“… 21 Several other clinical comparisons of suture repair vs wire fixation have reported satisfactory clinical outcomes but with fewer postoperative complications in suture methods. 23 28 …”
Section: Discussionmentioning
confidence: 99%